2021
DOI: 10.1111/1462-2920.15561
|View full text |Cite
|
Sign up to set email alerts
|

Biological production of H2, CH4 and CO2 in the deep subsurface of the Iberian Pyrite Belt

Abstract: Most of the terrestrial deep subsurfaces are oligotrophic environments in which some gases, mainly H 2 , CH 4 and CO 2 , play an important role as energy and/or carbon sources. In this work, we assessed their biotic and abiotic origin in samples from subsurface hard-rock cores of the Iberian Pyrite Belt (IPB) at three different depths (414, 497 and 520 m). One set of samples was sterilized (abiotic control) and all samples were incubated under anaerobic conditions. Our results showed that H 2 , CH 4 and CO 2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Samples from different subsurface settings have been previously used to investigate the abundance, nature, and substrate specific response of deep dwelling organisms via several cultivation-based methods and enrichment studies ( Kotelnikova and Pedersen, 1998 ; Hallbeck and Pedersen, 2008 , 2012 ; Fichtel et al, 2015 ; Rajala et al, 2015 ; Russell et al, 2016 ; Purkamo et al, 2017 , 2020 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ; Imachi et al, 2019 ; Sanz et al, 2021 ; Nuppunen-Puputti et al, 2022 ). The outcome of these studies, resulted in the enrichment of microorganisms mostly belonging to bacterial phyla Proteobacteria, Firmicutes, Actinobacteria, Chloroflexi and Bacteroidetes ( Rastogi et al, 2009 , 2013 ; Fichtel et al, 2012 ; Fortunato and Huber, 2016 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ) and archaeal members including Euryarchaeota, Thaumarchaeota and Crenarchaeota ( Zeng et al, 2009 ; Nuppunen-Puputti et al, 2018 ; Imachi et al, 2020 ; Alain et al, 2021 ; Courtine et al, 2021 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from different subsurface settings have been previously used to investigate the abundance, nature, and substrate specific response of deep dwelling organisms via several cultivation-based methods and enrichment studies ( Kotelnikova and Pedersen, 1998 ; Hallbeck and Pedersen, 2008 , 2012 ; Fichtel et al, 2015 ; Rajala et al, 2015 ; Russell et al, 2016 ; Purkamo et al, 2017 , 2020 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ; Imachi et al, 2019 ; Sanz et al, 2021 ; Nuppunen-Puputti et al, 2022 ). The outcome of these studies, resulted in the enrichment of microorganisms mostly belonging to bacterial phyla Proteobacteria, Firmicutes, Actinobacteria, Chloroflexi and Bacteroidetes ( Rastogi et al, 2009 , 2013 ; Fichtel et al, 2012 ; Fortunato and Huber, 2016 ; Rajala and Bomberg, 2017 ; Leandro et al, 2018 ) and archaeal members including Euryarchaeota, Thaumarchaeota and Crenarchaeota ( Zeng et al, 2009 ; Nuppunen-Puputti et al, 2018 ; Imachi et al, 2020 ; Alain et al, 2021 ; Courtine et al, 2021 ; Li et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to subsurface fluid-based studies, reactivation of inhabitant microbiota of Archean basement rocks has remained relatively less explored. Recently, deep subsurface studies on rock cores from Iberian Pyrite and a few other crystalline bedrocks and basalt samples from Deccan Traps have been carried out ( Dutta et al, 2018 , 2019 ; Leandro et al, 2018 ; Purkamo et al, 2020 ; Sanz et al, 2021 ; Sahu et al, 2022 ). However, reactivation and enrichment of deep endolithic microorganisms of the granitic bedrock are inadequately studied and their metabolic capabilities remain less known.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of occluded CH 4 in different samples and CH 4 produced after core samples activation, together with the presence of H 2 and CO 2 , the substrates for hydrogenotrophic methanogenesis, are strong indicators for the existence of methanogenic activities in the ecosystem. Recently, it has been shown that an important proportion of H 2 and CO 2 detected in the subsurface of the IPB are biologically produced (Mateos et al, 2022 ; Sanz et al, 2021 ). This observation is extremely important in our ecosystem because is generally assumed that most of the detected H 2 in the subsurface is abiotically produced (Pedersen, 1997 ; Stevens & McKinley, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…These colonies were also characterized by complementary imaging approaches, where sections prepared by focused ion beam scanning electron microscopy could be analyzed by nanoscale secondary ion mass spectrometry measurements to obtain elemental maps and show the colocalization of ions, such as 32 S − , 31 P − , and 12 C 14 N − , that were present in natural abundance in areas where stained cells were observed. Fluorescence in situ hybridization (FISH) techniques that use domain-or genera-specific probes, particularly techniques that enhance the levels of cell detection such as catalyzed-reporter deposition FISH and double-labeling of oligonucleotoide probes FISH, show great promise for imaging biofilms and microcolonies within rocks (Escudero et al 2018, Sanz et al 2021. FISH-based labeling can also be combined with lectin probes to differentiate cellular components, such as the differential distribution of proteins, lipids, and exopolysaccharides (Escudero et al 2018).…”
Section: Imaging the Endolithic Rock-hosted Biospherementioning
confidence: 99%